Social Grammatical Connotations in the Prose of Al-Hasan Al-Imam Al-Askari - احمد تغريد عبد الله; عباس سناء هادي (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The thought of Imam Hassan, peace be upon him, is one of the intellectual treasures of Islam. It is full of the principles of wisdom, the rules of ethics, and the essence of experiences. Grammatical significance is the major factor in extending the links of connection to social meanings that aim to achieve equality among members of society. We will find a close connection, as both express a comprehensive thought with a specific approach that seeks to free man and liberate him from social diseases.